Learn how to grow peppers - Ashilenje, Dennis S. (CTA / Phoenix Publishers Limited, 2014)
This book provides a step by step guide to production of pepper with much emphasis on outdoor conditions. It details planning, agronomic aspects and post harvest handling of this vegetable for marketing.